ANTI-GLOBALIZATION MOVEMENTS (Annual of the Faculty of Philosophy in Skopje, 2013)
ideological conflict of the past replaced the multitude of problems scattered around the world. They have caused major changes in political, economic and security plan and it appeared new, modern trends, directions and organizations of revolutionary character, willing to express their dissatisfaction processes of globalization. These developments have contributed to the internationalization of events and allowed the world to a global politically active. Using the dynamics of globalization have created strong momentum for transferring of power down and allow inclusion of people, groups and organizations with different views and ideologies and aimed makeover the neoliberal capitalist world system, the transformation of existing international organizations and institutions and finding a third way> that leads to responsible, just and democratic governance of globalization.
Keywords: ANTI-GLOBALIZATIΟΝ; MOVEMENTS; DISSATISFACTION; SOLIDARITY; ALTERNATIVES